2019
DOI: 10.1098/rstb.2019.0312
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of compositional meaning

Abstract: How do people create meaning from a string of sounds or pattern of dots? Insights into this process can be obtained from the way children acquire sentence meanings. According to the well-known principle of compositionality, the meaning of an expression is a function of the meanings of its parts and the way they are syntactically combined. However, children frequently seem to ignore syntactic structure in their sentence interpretations, suggesting that syntax is merely one of the sources of information constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In general, as summarized by Bates and Dick (2002), acquisition goes through distinctive, although partially overlapping stages: (multi)word comprehension (8–10 months), single word production (11–13 months), basic word combination (18–20 months), emergence of first functional words (24–30 months), and use of simple syntactic structures, including different types of sentences (i.e., declarative, interrogative, imperative; 30–34 months). Throughout the whole process, comprehension precedes production (Visser-Bochane et al, 2020), although an inverse pattern can be observed with regard to some specific aspects of language (e.g., word order or object pronouns; see Hendriks, 2020). Concerning the two domains of interest for our analysis (lexicon and syntax), word comprehension in children typically precedes expressive vocabulary acquisition (Messer, 2015; Roemer et al, 2019), just as syntax understanding precedes syntax production (Huttenlocher et al, 2002).…”
Section: Does Language Decline In Ageing Inversely Mirror Language Ac...mentioning
confidence: 99%
“…In general, as summarized by Bates and Dick (2002), acquisition goes through distinctive, although partially overlapping stages: (multi)word comprehension (8–10 months), single word production (11–13 months), basic word combination (18–20 months), emergence of first functional words (24–30 months), and use of simple syntactic structures, including different types of sentences (i.e., declarative, interrogative, imperative; 30–34 months). Throughout the whole process, comprehension precedes production (Visser-Bochane et al, 2020), although an inverse pattern can be observed with regard to some specific aspects of language (e.g., word order or object pronouns; see Hendriks, 2020). Concerning the two domains of interest for our analysis (lexicon and syntax), word comprehension in children typically precedes expressive vocabulary acquisition (Messer, 2015; Roemer et al, 2019), just as syntax understanding precedes syntax production (Huttenlocher et al, 2002).…”
Section: Does Language Decline In Ageing Inversely Mirror Language Ac...mentioning
confidence: 99%
“…(Bendy,et al, 2006). Hendriks (2019) conducts a study of how children create meaning from a series of patterns or sounds. Due to the concept of luminous formation, the meaning of a statement is a function of its parts meanings and their grammatical combination.…”
Section: Previous Workmentioning
confidence: 99%
“…movement) as well as for neurolinguistics. Finally, Hendriks [60] proposes that compositionality arises as a constraint on meaning in tasks that require coordination between speakers and hearers. She applies insights from optimality theory, and empirical data on asymmetries between comprehension and production in child language use, to derive the principle of compositionality from perspective taking: sentences may be guaranteed to have compositional meaning only when speakers take listeners into account.…”
Section: Questions and Themesmentioning
confidence: 99%